Cipta Cetak / Farhana Nabilah Mohd Hilmi .... [et al.] - Mohd Hilmi, Farhana Nabilah; Mohd Ghani, Muhamad Azzim Hakimi; Zairol Anuar, Nadia Emylia; Mokhter, Suriyati; Alim, Hendrry Win (2018)
Printing services really wide used in Malaysia especially among University's students. Many company had servicing on printing, photocopy, binding and many things for students requirement in University likewise in secondary school. In this study, Impian Teguh Ventures company had been chose to know how they built up from the bottom to top with their services provided. This company was introduced since Jun 2010 and the first shop under this company is Print Channel was founded in UiTM Puncak Alam at PSB level 4. The business scope that had been provided in this company were engineering and electrical, transportation and warehousing, printing services and general trading and supplies. There are 3 shop with different name were founded from this company which were Print Channel, Locus and ' Cipta Cetak' in UiTM Puncak Alam Campus. The owner of the company, Megat Nor Rashid Megat Ramli had started his business with small spaces with 5 personal computer for printing services and the enhancement of the business provided 10 to 16 personal computer located in Print channel and Cipta Cetak. The beginning of the business, financial and fix cost were the main weakness and the needs to be improved for maintaining their services. From the weakness itself, upgrading the business time to time with new strategies such as advertisement about their services provided, enhance in cater to the consumer, offering a host of products and services to help customer complete their personal business needs quickly and efficiently. Any competition with other printing services that had been located in same place not dropping the spirit is even a challenge to keep success in business.